Epigenetics in neurodegenerative disorders induced by pesticides - Yu, Guangxia; Su, Qianqian; Chen, Yao; Wu, Lingyan; Wu, Siying; Li, Huangyuan (Genes and environment, 2021)
Neurodegenerative diseases are becoming major socio-economic burdens. However, most of them still have no effective treatment. Growing evidence indicates excess exposure to pesticides are involved in the development of various forms of neurodegenerative and neurological diseases through trigger epigenetic changes and inducing disruption of the epigenome. This review summaries studies on epigenetics alterations in nervous systems in relation to different kinds of pesticides, highlighting potential mechanism in the etiology, precision prevention and target therapy of various neurodegenerative diseases. In addition, the current gaps in research and future areas for study were also discussed.